A Qualitative Study Exploring Community Pharmacists' Experiences and Views About Weight Management Interventions and Services in Klang Valley, Malaysia - Verma, Rohit Kumar; Chong, Wei Wen; Taha, Nur Akmar; Paraidathathu, Thomas (Frontiers in Public Health, 2021)
Objective: To qualitatively explore the perspectives of community pharmacists in Malaysia on their roles in weight management, and the barriers and facilitators in the expansion of these roles. Methods: A purposive sampling method was used to recruit community pharmacists in Klang Valley, Malaysia. Semi-structured individual interviews were conducted with community pharmacists, with an interview guide, from May 2018 to January 2019. The interviews were conducted in person (face-to-face). All interviews were audio-recorded with consent and transcribed verbatim. The interview transcripts were analyzed thematically, whereby emerging themes were coded and grouped into categories. Results: Twenty-four community pharmacists were recruited, with years of experience in pharmacy practice ranging from 2 to 40 years. Participants described their perceptions on the different weight management interventions where they emphasized the importance of a comprehensive lifestyle intervention and viewed that it should be the first-line intervention. Participants regarded their weight management service as easily accessible or approachable since community pharmacies are often the first point of call for patients seeking advice for their conditions before consulting doctors. Barriers identified by community pharmacists were mainly organizational in nature, which included lack of private consultation rooms, lack of time, and lack of qualified staff. Participants also described the need for training in weight management. Conclusion: Community pharmacists in Malaysia believed that they can positively contribute to the area of weight management. They cited multiple roles that they could play in weight management interventions and services. The roles cited include provision of education and advice, including on lifestyle modifications, drug therapy, weight loss products and supplements, and monitoring and providing referrals to other healthcare professionals. However, barriers would need to be addressed, including through pharmacist training, to strengthen and improve community pharmacists' roles and contributions in weight management service.